Isolated Bilateral Congenital Iris Sphincter Agenesis - Rao, Aparna (Hindawi Publishing Corporation, 2011)
Purpose. We herein report a patient with bilateral congenital total iris sphincter agenesis with no other abnormality detected on systemic examination. Methods. A 24-year-old laborer presented to us for a routine checkup with complaint of photophobia and inability to work under sunlight. Examination revealed bilateral absence of sphincter and 6.5 mm pupil in both eyes in the undilated state. Results. Accommodation was poor in both eyes. Systemic examination was within normal limits. He was prescribed bifocal photochromic glasses for constant wear. Conclusions. Congenital sphincter agenesis can occur in an isolated form without systemic abnormalities which can be managed conservatively.